Revitalisasi Dan Piloting Kantor Urusan Agama Di Indonesia (Dinamika Hukum Islam Berbasis Kemaslahatan) - Erfan, Zainul; Jalaluddin, Jalaluddin; Azhari, Fathurrahman; Hamdi, Fahmi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research examines the revitalization and pilot of the Office of Religious Affairs (KUA) in Indonesia, particularly in relation to the implementation of benefit-based Islamic law. The Ministry of Religious Affairs is under pressure to improve public services by embracing digitalization and making them more accessible. As a crucial part of the ministry's services, the KUA needs to reflect the commitment to nurturing the community. The revitalization involves digital applications for easier access to KUA services, improving infrastructure and human resources, and implementing good governance principles in e-government. The objective is to enhance the efficiency, transparency, and quality of public services. The digitalization efforts include online registration, information dissemination, consultations, digital document services, and monitoring and evaluation. The research findings indicate that the revitalization through digitalization strengthens public services, increases transparency, and meets the community's expectations for improved efficiency and accessibility. The efforts align with the KUA's functions and support the dynamics of Islamic law in Indonesia. Keywords: Revitalization, piloting, religious affairs office, Indonesia Abstrak Penelitian ini mengkaji revitalisasi dan uji coba Kantor Urusan Agama (KUA) di Indonesia, khususnya dalam kaitannya dengan implementasi hukum Islam berbasis kemaslahatan. Kementerian Agama berada di bawah tekanan untuk meningkatkan layanan publik dengan merangkul digitalisasi dan membuatnya lebih mudah diakses. Sebagai bagian penting dari layanan kementerian, KUA perlu mencerminkan komitmen untuk mengayomi masyarakat. Revitalisasi ini melibatkan aplikasi digital untuk memudahkan akses ke layanan KUA, meningkatkan infrastruktur dan sumber daya manusia, serta menerapkan prinsip-prinsip tata kelola yang baik dalam e-government. Tujuannya adalah untuk meningkatkan efisiensi, transparansi, dan kualitas layanan publik. Upaya digitalisasi tersebut meliputi pendaftaran online, penyebaran informasi, konsultasi, layanan dokumen digital, serta pemantauan dan evaluasi. Temuan penelitian menunjukkan bahwa revitalisasi melalui digitalisasi memperkuat layanan publik, meningkatkan transparansi, dan memenuhi harapan masyarakat untuk meningkatkan efisiensi dan aksesibilitas. Upaya-upaya tersebut sejalan dengan fungsi KUA dan mendukung dinamika hukum Islam di Indonesia. Kata Kunci: Revitalisasi, piloting, kantor urusan agama, indonesia